Timing of tofacitinib therapy is critical to improving outcomes in severe-critical COVID-19 infection: A retrospective study from a tertiary care hospital. Issue 43 (28th October 2022) - Kodali, Ramya; Umesh, Soumya; Selvam, Sumithra; Kamath, Deepak; Shobha, Vineeta
Abstract : Describe the use of tofacitinib in severe and critical coronavirus disease-2019 (COVID-19), and explore the association of drug initiation time with survival. A retrospective study of inpatients with severe or critical COVID-19 at a tertiary care hospital, who were prescribed generic tofacitinib for at least 48 hours, was conducted. Baseline demographics, comorbidities, illness severity, treatment, adverse effects and outcomes were analyzed. Patients were grouped based on median duration of symptomatic illness prior to tofacitinib administration, as early or late initiation groups. Forty-one patients ([85.4% males], mean age 52.9 ± 12.5 years), were studied. 65.9% (n = 27) had severe COVID-19, while 34.1% (n = 14) were critically ill. Death occurred in 36.6% patients (n = 15). The median time to prescription of tofacitinib was 13 (9.50, 16.0) days of symptom onset. Tofacitinib was initiated early (8–13 days) in 56.1% of patients (n = 23), while the remaining received it beyond day 14 of symptom onset (late initiation group). Multivariate logistic regression adjusted for age, presence of diabetes mellitus and illness duration prior to hospitalization demonstrated higher odds of survival (adjusted odds ratio 19.3, 95% confidence interval 2.57, 145.2) in the early initiation group, compared to the late initiation group. Early initiation of tofacitinib in severe and critical COVID-19 has potential to improve survival odds.